Planning Model and Questionnaire for Measuring MSME Performance through (TOE) Technology Organization Environment Indonesia - Siagian, Ade Onny; Riesmiyantiningtias, Ninuk; Amalia, Rizky (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
MSMEs (Micro, Small and Medium Enterprises) as one of the factors driving the economy in Indonesia are experiencing the Covid-19 pandemic crisis which has led to the activities of the Indonesian people. This will indirectly affect the activities of human life, including the buying and selling process. Buying and selling activities that are usually carried out face-to-face can not be carried out normally due to activities from the government so that it indirectly affects the sales results of business actors, including MSME actors. During this pandemic, there was a very significant decline and caused deep anxiety for MSME actors such as payment of employee salaries, daily operational costs, and others. The existence of this phenomenon or incident has resulted in MSMEs having to rack their brains in order to survive in the midst of the ongoing crisis. In order to continue to survive, MSMEs use social media to promote sales, or make sales online with social media. The purpose of this study was to determine the effect of social media adoption on the performance of MSMEs. This research method is carried out in several stages which include problems, literature review about the research model, research design, making instruments that produce questionnaires. The result of this study is produces a research model related to the adoption of social media on the performance of MSMEs which is supported by the dependent variable of the Technology-Organization-Environment (TOE) framework, as well as a questionnaire.